Pengaruh Kompetensi, Sistem Pengendalian Internal, Peran Perangkat Desa, dan Kualitas Penyajian Laporan Keuangan terhadap Akuntabilitas Pemerintah Desa dalam Mengelola Alokasi Dana Desa - Wahyu Ramadhan; Fefri Indra Arza (Universitas Negeri Padang, 2021)
This study aims to determine the Effect of Competence, Internal Control System, Role of Village Apparatus and Quality of Financial Statement Presentation on Village Government Accountability in Managing Village Fund Allocation (ADD) (Empirical Study in Nagari district of Solok). The data in this study used primary data obtained from the village apparatus. The sampling technique used random sampling method. The sample used in this study were 24 nagari in the district of Solok and the respondents were village officials who worked in the Wali Nagari office as many as 72 village officials. The village apparatus consists of the Village Head, Secretary, and Treasurer. Data analysis using multiple regression analysis. The results of this study indicate that (1) Competence has a positive and significant effect on Village Government Accountability in Managing Village Fund Allocations (ADD), (2) Internal Control System has a positive and significant impact on Village Government Accountability in Managing Village Fund Allocations (ADD), (3) The role of Village Apparatus has a positive and significant effect on Village Government Accountability in Managing Village Fund Allocations (ADD), (4) Quality of Financial Statement Presentation has a positive and significant impact on Village Government Accountability in Managing Village Fund Allocations (ADD).